ДОСЛІДЖЕННЯ ЕКОНОМІЇ ЕНЕРГЕТИЧНИХ І ВОДНИХ РЕСУРСІВ В СИСТЕМІ ВОДОПОСТАЧАННЯ БАГАТОПОВЕРХОВОГО БУДИНКУ ЗА ДВОРІВНЕВИХ СТОЯКІВ - Попович, О.М.; Яшин, Р.В. (Інститут електродинаміки НАН України, Київ, 2025)
The influence of the structure of the electromechanical water supply system of a 12-story building (replacing one riser with two risers of different levels) on the efficiency of energy and water resource use was studied. A mathematical model of the electromechanical system has been developed and implemented in software, which takes into account the dependence of the floor consumption on the pressure value and allows determining the water needs of consumers based on the given cyclorama of the water consumption of the house. According to the information about the known parameters of the basic version of the water supply system, the parameters of one floor and the parameters of the variants of the building system with risers for servicing floors are determined: 1-12; 1-6; 7-12. The study was carried out taking into account the proposed time dependence of the change in the input pressure of the house. Means of generalized determination of the energy efficiency of the asynchronous motor of the water supply system based on approximate dependences of nominal efficiency on power and efficiency on the degree of loading have been developed. The comparison of options was carried out according to the formulated expression of the efficiency criterion, as the ratio of the daily useful effect of the water supply system to consumers to the cost of electricity and water consumed during the given period. According to the simulation results, the two riser option provides savings of 4% of water and 25% of electricity with their ratio in monetary terms 6:1. This justifies the priority of taking into account water savings when justifying the modernization of water supply systems (parallel zoning, adjustable electric drive). References 11, table 1, figures 3.